President Ronald Reagan, Walter B. Wriston, and members of the Economic Policy Committee (Tufts Archival Research Center, 2008)
9.9 x 7.9. Picture taken in the White House Roosevelt Room. This date is approximate. The print and digital image were created from 'File2906' from the CD titled 'Walter B. Wriston Photographs - CD 5'.